Nystatin Regulates Axonal Extension and Regeneration by Modifying the Levels of Nitric Oxide - Roselló-Busquets, Cristina; Hernaiz-Llorens, Marc; Soriano, Eduardo; Martínez-Mármol, Ramon (Frontiers in Molecular Neuroscience, 2020)
Nystatin is a pharmacological agent commonly used for the treatment of oral, mucosal and cutaneous fungal infections. Nystatin has also been extensively applied to study the cellular function of cholesterol-enriched structures because of its ability to bind and extract cholesterol from mammalian membranes. In neurons, cholesterol level is tightly regulated, being essential for synapse and dendrite formation, and axonal guidance. However, the action of Nystatin on axon regeneration has been poorly evaluated. Here, we examine the effect of Nystatin on primary cultures of hippocampal neurons, showing how acute dose (minutes) of Nystatin increases the area of growth cones, and chronic treatment (days) enhances axon length, axon branching, and axon regeneration post-axotomy. We describe two alternative signaling pathways responsible for the observed effects and activated at different concentrations of Nystatin. At elevated concentrations, Nystatin promotes growth cone expansion through phosphorylation of Akt; whereas, at low concentrations, Nystatin enhances axon length and regrowth by increasing nitric oxide levels. Together, our findings indicate new signaling pathways of Nystatin and propose this compound as a novel regulator of axon regeneration.